Critical periods shaping the social brain: A perspective from Drosophila. - Dombrovski, M.; Condron, B. (BioEssays, 2021)
Many sensory processing regions of the central brain undergo critical periods of experience-dependent plasticity. During this time ethologically relevant information shapes circuit structure and function. The mechanisms that control critical period timing and duration are poorly understood, and this is of special importance for those later periods of development, which often give rise to complex cognitive functions such as social behavior. Here, we review recent findings in Drosophila, an organism that has some unique experimental advantages, and introduce novel views for manipulating plasticity in the post-embryonic brain. Critical periods in larval and young adult flies resemble classic vertebrate models with distinct onset and termination, display clear connections with complex behaviors, and provide opportunities to control the time course of plasticity. These findings may extend our knowledge about mechanisms underlying extension and reopening of critical periods, a concept that has great relevance to many human neurodevelopmental disorders.